Analyzing Sartrean Inter-subjectivity and Concept of the Look in Macbeth - Masoomeh Rahmani Goldareh; Fazel Asadi Amjad (Ideas: Journal of English Literary Studies)
Shakespeare and Sartre have a specific bond in that the Bard portrayed the kind of tragic characters that can be the embodiment or conceptualization of existential notions. The present research intends to investigate the relations of two consciousnesses or the Sartrean inter-subjectivity as depicted in Macbeth and between its tragic heroes and others. Others have a great impact on Macbeth’s consciousness and his process of self-formation. When he chooses to commit murder, he attempts to conceal his crimes from others to shun the heavy sense of shame and self-disgust (guilt) created through what Sartre calls the concept of the Look and its alienating effect upon the individual. Macbeth's social self (being-for-others), which is portrayed in his outward relations with others, is in stark contrast with his subjective self (being-for-itself), which is displayed in his myriad reflections in his soliloquies and asides. The Macbeths assume a mask to conceal their real self from others’ consciousnesses. This article first explains the concepts of inter-subjectivity and the Look in Sartre's philosophy, and then it discusses the same notions in the context of Shakespeare's Macbeth.